Experimental Study on a Hybrid Coupling Beam With a Friction Damper Using Semi-steel Material - Wang, Tao; Yang, Fengli; Wang, Xin; Cui, Yao (Frontiers in Materials, 2019)
RC coupling beams have been reported serious damages during 2008 Wenchuan earthquake. Once cracks occurred, it is very difficult to repair. To improve the ductility and reparability of the traditional RC coupling beam, a damage-controllable hybrid coupling beam is proposed in this study. The hybrid coupling beam couples the wall limbs by a friction damper connected through steel beam segments. The strength and stiffness of the friction damper are carefully designed to concentrate more deformation in the damper. The friction mechanism could dissipate more energy than the traditional RC coupling beam. And the uncertainties introduced by the design process and the inherent characteristics of traditional RC coupling beams or other types of dampers are significantly reduced. High-strength bolts are used for all connections, so that it could be quickly replaced once any damage is observed after an earthquake. In this study, a friction damper using semi-metallic friction plates and stainless-steel shims as the contact pair was tested at different loading rate. The temperature was measured. A thermal-mechanical model was then developed to correlate the dissipated energy with the friction coefficient or friction force, which can be easily incorporated into the structural design process. Finally, the hybrid coupling beam was designed and tested quasi-statically. The force, deformation, and energy dissipation capacity were compared with the traditional RC coupling beam, which also demonstrated the damage controllability by using the propose hybrid coupling beam.